The evaluation of ergonomic risk factors among meat cutters working in Jabalpur, India. (September 2015) - Mukhopadhyay, Prabir; Khan, Amaltas
Abstract : Background: Manual meat cutters in India are at high risk of work-related musculoskeletal disorders (WMSDs) for a variety of reasons including holding awkward postures, repetitive forceful exertions, and inadequate rest. This is the first study of its kind to investigate the nature and magnitude of WMSDs among manual meat cutters in India. Objective: The aim of this study was to measure the ergonomic risk factors for WMSDs among adult male manual meat cutters working in Jabalpur, India. Methods: We used direct observation, activity analysis, questionnaires, interviews, photography, and video to measure the quantitative ergonomic risk factors. Results: Ovako working posture analysis indicated high scores (four for the back in peeling, six for the arms in cutting, and six for the arms during mincing tasks). Rapid entire body assessment method (REBA) scores were also high at 10/10 for deboning and mincing tasks, all associated with repetitive movements of the arms and awkward posture of the upper part of the body. Conclusions: The study indicates that most tasks for meat cutters fall in the high-risk category for occupational injury. Results suggest that ergonomic interventions that address retooling and workstation and process redesign would be useful in reducing the number of injuries.